A Brief Overview of the History of Kokand (Origins of Museums) - Toʻraqulova, Nigora (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the governance of the Kokand Khanate, its historical development, its conquest by other states, and the cultural heritage within its territory, particularly museums and their origins. It also discusses their significance.